EFFECT OF EDUCATIONAL INTERVENTION ON FAMILY SUPPORT FOR PREGNANT WOMEN IN PREVENTING ANEMIA - Mira Triharini; Ni Ketut Alit Armini; Aria Aulia Nastiti (Belitung Nursing Journal, 2018)
Background: Anemia during pregnancy is a major nutritional problem that can cause health problems for mothers and their fetus. Prevention of anemia has been done but many obstacles are perceived by pregnant women. Families need to provide support to improve the prevention behavior of anemia. Objective: This research aims to explore the effect of educational intervention on family support for pregnant women in preventing anemia. Methods: A quasi-experimental design was carried out on 60 pregnant women who had done pregnancy checkups at Community Health Centre and had received iron supplement, in which 30 women were in the experimental group and the rests were in the control group. This study was conducted from December 2016 to January 2017. Family support was measured using questionnaires before and after educational intervention. Results: After educational intervention, there was a significant change from the pretest score to the posttest score in the experimental group (p<0.05). There was an increase in the average score in the experimental group, 14.47 ± 2.89 becomes 16.83 ± 2.32. Conclusion: Educational interventions can increase family support for maternal behavior in preventing pregnancy anemia such as improving adherence to taking iron supplements and high intake of food containing iron.